Deferral Versus Performance of Revascularization for Coronary Stenosis With Grey Zone Fractional Flow Reserve Values: A Systematic Review and Meta-Analysis. (January 2020) - Du, Yu; Liu, Yan; Cai, Gaojun; Yang, Bangguo; Cheng, Yujing; Liu, Jinxing; Liu, Wei; Liu, Xiaoli; Zhou, Zhiming; Zhao, Yingxin; Zhou, Yujie
We searched PubMed, EMBASE, Cochrane Library, and Web of Science for studies using fractional flow reserve (FFR) to determine whether revascularization should be performed or deferred for patients with coronary stenosis and grey zone FFR. Meta-analysis was performed using the generic inverse variance method, and hazard ratios (HR) were synthesized with a random-effects model. Of 2766 records, 7 nonrandomized studies including 2683 patients were selected. The pooled results demonstrated, during a median follow-up of 32 months, that revascularization significantly reduced the risk of major adverse cardiac events (MACE; 7 studies: HR [95% confidence interval, CI]: 0.65 [0.45-0.93], P = .02) and target vessel revascularization (TVR; 4 studies: HR [95% CI]: 0.52 [0.36-0.76], P < .01). Whereas revascularization was not significantly superior in terms of all-cause death (3 studies: HR [95% CI]: 0.56 [0.26-1.22], P = .14), cardiac death (2 studies: HR [95% CI]: 0.57 [0.16-2.01], P = .38), myocardial infarction (MI; 4 studies: HR [95% CI]: 1.03 [0.26-4.03]), and all-cause death or MI (3 studies: HR [95% CI]: 0.66 [0.20-2.19], P = .50). Therefore, revascularization appeared to be superior to deferral for patients with grey zone FFR in MACE and TVR, while hard end points did not show such significance. This work was registered in PROSPERO (CRD42019118432).